Characterization of Four Outer Membrane Proteins Involved in Binding Starch to the Cell Surface of Bacteroides thetaiotaomicron - Shipman, Joseph A. (American Society for Microbiology, 2000)
Bacteroides thetaiotaomicron, a gram-negative obligate anaerobe, utilizes polysaccharides by binding them to its cell surface and allowing cell-associated enzymes to hydrolyze them into digestible fragments. We use the starch utilization system as a model to analyze the initial steps involved in polysaccharide binding and breakdown. In a recent paper, we reported that one of the outer membrane proteins involved, SusG, had starch-degrading activity but was not sufficient for growth on starch. Moreover, SusG alone did not have detectable starch binding activity. Previous studies have shown that starch binding is essential for starch utilization. In this paper, we report that four other outer membrane proteins, SusC through SusF, are responsible for starch binding. Results of (14)C-starch binding assays show that SusC and SusD both contribute a significant amount of starch binding. SusE also appears to contribute substantially to starch binding. Using affinity chromatography, we show in vitro that these Sus proteins interact to bind starch. Moreover, protease accessibility of either SusC or SusD greatly increased when one was expressed without the other. This finding supports the hypothesis that SusC and SusD interact in the outer membrane. Evidence from additional protease accessibility studies suggests that SusC, SusE, and SusF are exposed on the cell surface. Our results demonstrate that SusC and SusD act as the major starch binding proteins on the cell surface, with SusE enhancing binding. SusF's role in starch utilization has yet to be determined, although the fact that starch protected it from proteolytic attack suggests that it does bind starch.